Hormonal regulation of mannan-binding lectin synthesis in hepatocytes - Sørensen, C M (Blackwell Science Inc, 2006)
Activation of the complement system via the plasma protein mannan-binding lectin (MBL) provides a first line of defence against infections. The plasma level of MBL is, in part, determined genetically, but may also be influenced by different hormones in vivo. Here we study the hormonal regulation of MBL synthesis from the human hepatocyte cell line HuH-7. Cells were exposed to medium with growth hormone (GH), hydrocortisone, insulin-like growth factor (IGF)-1, insulin, interleukin (IL)-6 or thyroid hormones (T3 or T4). After 3 days the concentration of MBL in the culture supernatants was determined and the amount of mRNA for MBL was measured, relative to mRNA for β2 microglobulin. GH, IL-6, T3 and T4 significantly increased MBL synthesis in a dose-dependent manner, while hydrocortisone, insulin and IGF-1 had no effect. T3 caused a fourfold increase at 1 nM of T3 (P < 0·001) and at 100 nM of T3 the production was increased more than eightfold. The effect of T4 was less potent, reaching an eightfold increase at 1 µM of T4 (P < 0·001). GH augmented the production of MBL threefold at a concentration of 100 ng/ml (P = 0·018) with no further effect up to 10 µg/ml, whereas IL-6 caused only a very weak increase in MBL production. MBL mRNA levels were stable during the first 24 h of T3 stimulation but increased significantly between 24 and 48 h. The results suggest that MBL synthesis in humans may be increased by thyroid hormone and GH, whereas it does not exhibit a classical IL-6-dependent response.